A cubic silsesquioxane modified with purpald®: Preparation, characterization and a voltammetric application for determination of sulfite - Soares, Layciane Aparecida [UNESP] (2013)
A novel composite formed by interaction of a octa(3-chloropropyl)octasilsesquioxane modified with Purpald®, and its subsequent reaction with silver and hexacyanoferrate (III) (AgHSP), was synthesized and initially characterized by Fourier transform infrared spectra (FTIR) and cyclic voltammetry. The cyclic voltammogram of the modified graphite paste electrode with AgHSP, showed one redox couple with formal potential Eθ'=0.64V (vs Ag/AgCl, KNO3, 1.0 mol L-1; v = 20 mV s-1), attributed to the Fe2+(CN)6/ Fe3+(CN)6 process. The redox couple presents an electrocatalytic response for determination of sulfite. The modified electrode showed a linear response from 7.0×10-5 to 1.0×10-3 mol L-1 with the corresponding equation Y(μA) = 18.05 + 29.983×103 [sulfite], and a correlation coefficient of r=0.999. The method showed a detection limit of 0.115×10-4 mol L-1 with a relative standard deviation of ± 4% (n = 3) and amperometric sensitivity of 29.983×10-3A mol L-1. The modified electrode showed a excellent stability and good reproducibility during experiments. © 2013 by ESG.